2005
DOI: 10.1002/jor.20002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GDF‐5 on ligament healing

Abstract: The effects of growth and differentiation factor-5 (GDF-5) on ligament healing were studied using a gap injury model of the medial collateral ligament in rat knee joints. The administration of GDF-5 once at the time of surgery significantly improved the mechanical properties of the femur-ligament-tibia complex. At 3 weeks after surgery, 30 mg of GDF-5 improved the ultimate tensile strength of the complex by 41%, and the stiffness by 60%, compared with the vehicle control ( p < 0.05 for both; Fisher's PLSD test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…In conclusion, the BPC 157 ligament healing may be clinically relevant (i.e., no knee joint contracture, no obvious valgus instability, preserved muscle motor function and walking pattern), thus, the significant knee joint failure counteracted (as important proof of the activity that is lacking in the standard peptide studies 3,14,16,17,18 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In conclusion, the BPC 157 ligament healing may be clinically relevant (i.e., no knee joint contracture, no obvious valgus instability, preserved muscle motor function and walking pattern), thus, the significant knee joint failure counteracted (as important proof of the activity that is lacking in the standard peptide studies 3,14,16,17,18 ).…”
Section: Discussionmentioning
confidence: 97%
“…Function in either condition, normal (walking rats) and stressed (running rats), biomechanic, macro/microscopy were noted superior as before [1][2][3][4][5][6][7][8][9][10][11][12] in tendon studies 1,2,10 and other wound studies, 4,9,10,12 , not species related. This may be a wound healing (not found with standard peptide factors 3,16,17 ) more apt to predispose the ligament to improved healing course after transection. Anyway, such parallelism (but, no overlap) in the BPC 157 healing of ligament or tendon, after transection or detachment and in bone-healing, 1-12 is complementary to improvement (biomechanical, functional, microscopic/immunochemical, macroscopic) with multiple modes of therapy regimens and the ligaments providing structural support around joint capsules and at sites where bones make contact with other bones.…”
Section: Discussionmentioning
confidence: 99%
“…More notably, decreased collagen content and tensile strength [37], as well as delayed healing, have been reported in the Achilles tendon of GDF-deficient mice [13]. Conversely, exogenous GDF protein delivered by carrier [3,46], suture coating [43], or adenoviral transfection [44] improves tendon healing and tensile strength of transected tendons.…”
Section: Discussionmentioning
confidence: 99%
“…1,6,7 Individual growth factors have different effects on different cells during the healing process, and certain growth factors regulate the expression of other growth factors through both autocrine and paracrine feedback loops. 1,6 Several studies have demonstrated beneficial effects of selected growth factors on aspects of ligament healing, including platelet-derived growth factor (PDGF), 8,9 insulin-like growth factor (IGF), 8 transforming growth factor beta-1 and 2 (TGF-b1 and 2), 9,10 and growth and differentiation factor-5 (GDF-5), 11 when used alone or in multiple application. Nevertheless, it remains unclear what factors play the key roles in promoting ligament healing, which growth factor has the maximum effect, or what combinations might create synergistic effects.…”
Section: Growth Factors Promote Ligament Healingmentioning
confidence: 99%